Determining the kinetic and optimum characteristics of glucose oxidase immobilized on polyurethane - Kalay Şaban (Türk Biyokimya Dergisi, 2024)
The primary aim of this study is to immobilize glucose oxidase (GOX) as a model enzyme using a simple and efficient method without the use of any toxic chemicals. This will enable the multiple reusability of GOX, thereby reducing the process cost. Furthermore, the objective is to determine the kinetic, optimum pH, and temperature parameters in comparison to soluble GOX.